Natural medicine in neuroprotection for ischemic stroke: Challenges and prospective - Tao, Tao; Liu, Maozhu; Chen, Mengyuan; Luo, Ying; Wang, Cheng; Xu, Tongtong; Jiang, Yixu; Guo, Yiyan; Zhang, John H. (Pharmacology & therapeutics (Oxford), 2020)
There is a growing interest in using natural medicines to treat stroke as the leading cause of disability worldwide. Especially plant-derived natural medicines have multiple beneficial effects, including antioxidative, anti-inflammatory, antiapoptotic, suggesting their potential for stroke treatment. However, failure in clinical translation has created a substantial challenge for their use as stroke treatment. This review summarises the status of using natural medicinal formulations in stroke treatment, as well as the challenges. Although natural medicines have excellent prospects for ischaemic stroke treatment, several concerns need to be addressed for translating the success in animal research to humans. Specifically, there should be more considerations for investigating the precise mechanisms of natural medicines mediating the neuroprotective effects on stroke. Moreover, to further improve the prospects of clinical translation, further studies should be performed in aged animals rather than young adult animals.